Interactions of Monetary and Macroprudential Policies in a Model of the Korean Economy - Elena Afanasyeva; Meral Karasulu (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We use a microfounded dynamic stochastic general equilibrium (DSGE) model with banks to study interactions between monetary and macroprudential policies in a small open economy. The model is calibrated/estimated for Korea. Cooperation of monetary and macroprudential policies is optimal under a financial shock. Prolonged periods of monetary accommodation lead to inflationary pressures, lower the effectiveness of macroprudential instrument (loan-to-value ratio) and contribute to further credit growth, increasing vulnerabilities.
Keywords: E58; E61; G28; 330